Implementation of Steganography Image System on Android Using LSB Embedding Method - Dhilega, Yodiaz Gilby; Md Nor, Danial; MT., Istiadi ST. (Evolution in Electrical and Electronic Engineering, 2020)
Steganography implementation in digital security is still used today as an effort to maintain data security. Least Significant Bit is implemented on the android device as an important aspect of digital security application and for easier use of the method. Least Significant Bit is dependent on the size of the image, pixel composition, and file size to maintain the data embedded into each last bit of the pixel. The idea of this research is to build the implementation of Least Significant Bit using Steganography Image System on the Android Platform. Thus, in this, every research aspect of the stego image is tested to check whether the image could maintain its embedded data through various ways of direct cybersecurity attack while measuring the quality of stego image with the cover image by using Java Language, which extremely simple and powerful high-level programming language. From six samples with different resolutions, vary from 120px width to 184px, the stego image was tested by inserting 16 string characters into the cover image. The Least Significant Bit is able to embed the string characters into cover image successfully without making any changes that perceivable by human eyes. The PSNR method is used to verify the digital image properties from the prepared sample. The result shows that the average value of PSNR of 120px to 184px width stego image is 20 dB.